PENGEMBANGAN VIDEO PETUNJUK LATIHAN KEKUATAN KREATIF BAGI MAHASISWA PADA ERA PANDEMI COVID - 19 - Sari Siti Robiatul Awaliyah, - (2020)
The aim of this study is to create a strength training instructional video that can be used as a training media for the students in the Covid-19 era. This study uses Design and Development (D&D) research with 6 stages of research procedures, namely: (1) problem identification (2) describing objectives (3) design and development of the product (4) product testing (5) evaluation after testing (6) Conclusion. The research instrument used the Expert Validity Test and Video View Test on students using a questionnaire. The results of the expert's assessment show that this video product can be categorized as a very good and interactive media after several revision stages and suggestions from sports experts and multimedia experts have been carried out. The results of the assessment from the broadcast test to the student virtual community also show that this media is very good and adds motivation. The study presents recommendations and a collection of strength training exercises to get more excited to exercise during the Covid-19 pandemic.